• $V = a\cdot b\cdot c$
1 2
$a = \frac{ V}{b\cdot c}$
1 2
$b = \frac{ V}{a\cdot c}$
1 2
$c = \frac{ V}{b\cdot a}$
1 2
$O = 2\cdot (a\cdot b + a\cdot c + b\cdot c)$
1 2
$a = \frac{O-2\cdot b\cdot c}{2\cdot (b+c)}$
1 2
$b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)}$
1 2
$c = \frac{O-2\cdot b\cdot a}{2\cdot (b+a)}$
1 2
$d = \sqrt{a^{2} +b^{2} +c^{2} }$
1 2
$a = \sqrt{d^{2} -b^{2} -c^{2} }$
1 2
$b = \sqrt{d^{2} -a^{2} -c^{2} }$
1 2
$c = \sqrt{d^{2} -b^{2} -a^{2} }$
1 2

Beispiel Nr: 02
$\text{Gegeben:}\\\text{Länge} \qquad a \qquad [m] \\ \text{Breite} \qquad b \qquad [m] \\ \text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Höhe} \qquad c \qquad [m] \\ \\ c = \frac{O-2\cdot b\cdot a}{2\cdot (b+a)}\\ \textbf{Gegeben:} \\ a=4m \qquad b=7m \qquad O=1m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ c = \frac{O-2\cdot b\cdot a}{2\cdot (b+a)} \\ a=4m\\ b=7m\\ O=1m^{2}\\ c = \frac{1m^{2}-2\cdot 7m\cdot 4m}{2\cdot (7m+4m)}\\\\c=-2\frac{1}{2}m \\\\\\ \small \begin{array}{|l|} \hline a=\\ \hline 4 m \\ \hline 40 dm \\ \hline 400 cm \\ \hline 4\cdot 10^{3} mm \\ \hline 4\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline b=\\ \hline 7 m \\ \hline 70 dm \\ \hline 700 cm \\ \hline 7\cdot 10^{3} mm \\ \hline 7\cdot 10^{6} \mu m \\ \hline \end{array} \small \begin{array}{|l|} \hline O=\\ \hline 1 m^2 \\ \hline 100 dm^2 \\ \hline 10^{4} cm^2 \\ \hline 10^{6} mm^2 \\ \hline \frac{1}{100} a \\ \hline 0,0001 ha \\ \hline \end{array} \small \begin{array}{|l|} \hline c=\\ \hline -2\frac{1}{2} m \\ \hline -25 dm \\ \hline -250 cm \\ \hline -2,5\cdot 10^{3} mm \\ \hline -2,5\cdot 10^{6} \mu m \\ \hline \end{array}$